COVID-19 Prognosis in Association with Antidepressant Use - Min, Kyung Hyun; Kim, Tae Hyeok; Oh, Soo Jin; Kim, Woorim; Lee, Kyung Eun (Pharmacopsychiatry, 2022)
Introduction Various subtypes of severe acute respiratory syndrome coronavirus 2 and variations among immune systems in different ethnicities need to be considered to understand the outcomes of coronavirus disease 2019 (COVID-19). This study aimed to provide evidence for the association between the use of antidepressants and the severity of COVID-19.Methods We used the National Health Information Data-COVID database. Patients with one or more prescriptions of any antidepressant were selected as the exposure group. Detailed analyses were performed to determine the type of medication associated with the prognosis.Results The use of selective serotonin reuptake inhibitors (SSRIs) was associated with a lower risk of severe outcomes of COVID-19, whereas the use of tricyclic antidepressants (TCAs) increased the risk of poor prognosis of COVID-19. Detailed analyses showed that escitalopram was significantly associated with better clinical outcomes, and nortriptyline was linked to more severe COVID-19 outcomes.Conclusion This study revealed an association between antidepressants and COVID-19 prognosis. SSRIs were significantly associated with a lower risk of severe outcomes, whereas TCAs were related to the poor prognosis of COVID-19.
Keywords: COVID-19; antidepressants; SSRI; TCA